Vibration signal modeling of a planetary gear set for tooth crack detection. (February 2015) - Liang, Xihui; Zuo, Ming J.; Hoseini, Mohammad R.
Highlights: Vibration signals of a planetary gear set are modeled considering multiple vibration sources and effect of transmission path. Fault symptoms are revealed when there is a crack in the sun gear. The proposed approach is experimentally verified. Abstract: In a planetary gearbox, there are multiple vibration sources, and the transmission path of vibration signals changes due to the rotation of the carrier. This study aims to model the vibration signals of a planetary gearbox and investigate the vibration properties in the healthy condition and in the cracked tooth condition. A dynamic model is developed to simulate the vibration source signals. A modified Hamming function is proposed to represent the effect of the transmission path. By incorporating the effect of multiple vibration sources and the effect of transmission path, resultant vibration signals of a planetary gearbox are obtained. Through analyzing the resultant vibration signals, some vibration properties of a planetary gearbox are revealed and the fault symptoms of sun gear tooth crack are identified and located. Finally, the proposed approach is experimentally verified.